Steatotic liver disease and chronic viral hepatitis - Janczura, Jakub; Mangia, Alessandra; Dobrowolska, Krystyna; Brzdęk, Michał; Brzdęk, Kinga; Wajdowicz, Małgorzata; Gorczyca-Głowacka, Iwona; Stępień, Piotr M.; Zarębska-Michaluk, Dorota (Clinical and Experimental Hepatology, 2025)
Steatotic liver disease (SLD) is a condition characterized by excessive fat accumulation within hepatocytes. In recent years, the nomenclature and diagnostic framework of the disease have evolved and the term SLD has replaced the previous fatty liver disease classification. This change reflects a more inclusive understanding of the metabolic drivers of the disease and its strong association with systemic conditions. With the rising global prevalence of metabolic disorders, the burden of SLD has increased significantly, making it the leading cause of chronic liver disease worldwide. While many cases of SLD remain non-progressive, metabolic dysfunction associated steatohepatitis (MASH) may advance to fibrosis, cirrhosis, or hepatocellular carcinoma. The risk of disease progression may be greater when liver steatosis coexists with other hepatic insults, particularly chronic infections with hepatitis B virus or hepatitis C virus. This review explores the prevalence, interactions, and therapeutic implications of SLD in patients with chronic viral hepatitis.